The empirical content of marital surplus in matching models - Karina Doorley; Arnaud Dupuy; Simon Weber (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This note investigates the extent to which structural estimates of marital surplus are informative about subjective well-being and separation. We first estimate the marital surplus using a simple matching model of the marriage market with perfectly transferable utility and heterogeneity in tastes applied to a rich German panel dataset. We then show that these estimates of the marital surplus are negatively correlated with separation and the difference in spouses' subjective satisfaction.
Keywords: C78; D1; 330; matching market; marital surplus; subjective well-being; separation